Adipose-derived stem cells undergo spontaneous osteogenic differentiation in vitro when passaged serially or seeded at low density. (3rd July 2016) - Liu, Y; Zhang, Z; Zhang, C; Deng, W; Lv, Q; Chen, X; Huang, T; Pan, L
Abstract : Adipose-derived stem cells (ADSCs) are a convenient source of cells for regenerating tissue. Widespread application of ADSCs requires that they propagate efficiently and differentiate in vitro. We investigated the differentiation potential of ADSCs during long-term expansion in vitro and when the cells were seeded at low density. ADSCs were isolated from the inguinal fat pads of 3-week-old male rats, then cultured serially for 12 passages; some ADSCs at passage 3 were seeded at low density. The differentiation potential of ADSCs from passage 3 to passage 12 was assessed by their capacity for adipogenesis and osteogenesis while cultured in specific induction media. Spontaneous osteogenesis of ADSCs at passage 12 and of ADSCs that were seeded at low density was detected by western blotting, alizarin red S staining and measurement of alkaline phosphatase (ALP) activity. We found that with increasing passage number, the adipogenic potential of ADSCs decreased and osteogenic differentiation increased. Alizarin red S staining, bone morphogenetic protein-2 (BMP-2) and runt-related transcription factor 2 (Runx2) expressions, and ALP activity demonstrated that both ADSCs at passage 12 and those that were seeded at low density differentiated into osteoblasts without additional induction factors.